Design And Development Of Weaving Aid Tool For Rattan Handicraft - Abdullah, Zulkeflee; Janin @ Abd. Karim, Nurul Fadzlina; Md Ali, Mohd Amran; Shamsudin, Shamsul Anuar; Kasim, Mohd Shahir; Samat, Khairul Fadzli (Trans Tech Publications, 2015)
-